Engenharia simultânea: planejamento e controle integrado do processo de produção/projeto na construção civil - Pedrini, Manuela Kautscher (2012)
The term Concurrent Engineering (CE) designates several concepts with the purpose of optimizing the time spent in the production of manufactured goods. Although this term has not been incorporated in the construction industry, studies about the management of building projects incorporate many of its ideas. The goal of my work is to discuss the application of CE within Civil Engineering, more specifically to study its suitability in the projects of the construction of buildings and to propose a framework to apply CE’s concepts in the design phase of the project. The motivation of my research derives from the current scenario of the construction industry in Brazil, in which construction companies have been searching for technological innovations in the process of developing new products. I used two case studies to assess the current state of the design process. Questionnaires and technical summaries served to identify the phases more likely to be optimized by CE, and to pinpoint the difficulties in applying CE. Results indicate that there is space to improve the new product development process, and that the adoption of CE is an alternative to provide such improvements.